An extended analytical model for predicting the compressive failure behaviors of composite laminate with an arbitrary elliptical delamination. (1st March 2020) - Wang, Kangkang; Zhao, Libin; Hong, Haiming; Zhang, Jianyu; Hu, Ning
Abstract: Delamination is one of the most serious failure modes in carbon fiber reinforced composite laminates, because it can reduce the overall stiffness, which further leads to premature structural buckling and failure at loads below the design level. Arbitrary elliptical delamination is the most representative case in engineering practice, and the delamination propagation and failure behaviors are much complicated. To completely evaluate the compressive failure behaviors of composite laminate with arbitrary elliptical delaminations, an extended analytical model was established based on the first order shear deformation theory and brittle fracture mechanics. The analytical model innovatively incorporated the failure evaluation, and especially the delamination propagation path into buckling analysis of composite laminate containing an arbitrary elliptical delamination. The predicted results are highly consistent with the outcomes of uniaxial compression tests, thus validating the applicability and accuracy of the analytical model as a highly efficient tool in engineering practices for the most representative arbitrary elliptical delamination problems. It is found that the propagation of the elliptical deamination in composites was fast and unstable, which led to catastrophic failures. The delamination propagation tends to initiate from the delamination boundary points with the maximum transverse coordinates and propagate transversely to the loading direction.